2013
DOI: 10.1245/s10434-013-2975-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications influence recurrence and survival after resection of hepatic colorectal metastases

Abstract: In this selected cohort of patients from a previous RCT, perioperative morbidity was strongly (and independently) associated with cancer-specific outcome. It also was associated with delayed initiation of postoperative chemotherapy, the impact of which on survival is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 21 publications
8
54
0
Order By: Relevance
“…Evidence from breast, colorectal and pancreatic cancer has shown that delays in receipt of adjuvant therapy negatively impacts disease-free survival, disease-specific survival and overall survival. [27][28][29][30] Given the importance of systemic therapy in gastric cancer survival, minimizing postoperative morbidity in order to get patients, in a timely manner, to their intended oncologic therapy is paramount. 2,31 We identified RBCT as being associated with increased postoperative morbidity and thus as a potentially modifiable factor that can be addressed to improve gastric cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from breast, colorectal and pancreatic cancer has shown that delays in receipt of adjuvant therapy negatively impacts disease-free survival, disease-specific survival and overall survival. [27][28][29][30] Given the importance of systemic therapy in gastric cancer survival, minimizing postoperative morbidity in order to get patients, in a timely manner, to their intended oncologic therapy is paramount. 2,31 We identified RBCT as being associated with increased postoperative morbidity and thus as a potentially modifiable factor that can be addressed to improve gastric cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Allogenic blood transfusions may impair normal immune modulatory functions that further contribute to negative outcomes. [33][34][35][36][37] As a result, oncologic outcomes also may be compromised by receipt of blood transfusions due to alterations of host immunity. 13,33,36,37 A study from the National Cancer Institute demonstrated that each additional unit of blood transfused in the perioperative period increased the risk of disease recurrence by 5% and death by 7% in patients undergoing partial hepatectomy for colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[9-12] Furthermore, postoperative morbidity has been linked with worse long term oncologic outcomes in patients undergoing resection for cancer, which remains the most common indication for liver resection. [13-17] While operative and patient specific factors are related to postoperative morbidity, there are few modifiable factors associated with the development of postoperative morbidity in these patients.…”
Section: Introductionmentioning
confidence: 99%